Institution building down on the farm - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
study visit leaders of young farmers' organisations from West and Central Africa, and Madagascar spent 10 days in November 1998 visiting counterpart organisations and farms in southern and eastern France